Localization of the spectrum and representation of solutions of linear dynamical systems - Mazko, A. G. (Ukrains’kyi Matematychnyi Zhurnal, 1998)
We develop a general method for the localization of eigenvalues of matrix polynomials and functions based on the solution of matrix equations. For a broad class of equations, we formulate theorems that generalize the known properties of the Lyapunov equation. A new method for the representation of solutions of linear differential and difference systems is proposed.